Child Gender and Parental Investments In India: Are Boys And Girls Treated Differently? - Barcellos, Silvia Helena (2014)
Previous research has not always found that boys and girls are treated differently in rural India. However estimates of the effect of gender on parental investments could be biased if girls end up in larger families due to son-biased stopping rules. Using a novel identification strategy that exploits that gender at conception is random, we document that boys receive more childcare time than girls, they are breastfed longer and they get more vitamin supplementation. Compared to other developing countries, boys have an advantage in height and weight relative to girls. Neither greater needs nor anticipated family size explain the results.